Formulation and evaluation of liposomal films for buccal delivery of antiretroviral drug - Okafor, Nnamdi Ikemefuna (Rhodes University, Faculty of Science, Department of Chemistry, 2020)
The human immune deficiency virus (HIV) infection has been ranked as one of the most devastating microbial infections in the world. This status is a result of the HIV rapid genetic variation, which limits discovery of a vaccine. Use application of antiretroviral therapy (ARVT) in treatment of the disease caused by the HIV infection (known as acquired immunodeficiency syndrome, HIV-AIDS) is frequently compromised by several factors such as the low bioavailability and severe adverse effects associated with the existing antiretroviral drugs (ARVDs). This underlines the need for controlling the pharmacokinetics profiles of ARVD using effective vehicles that can modify drug biodistribution. The same is true for many other conditions, where delivery systems can determine the success or failure of treatment by controlling pharmacokinetic and dynamic properties. The mucosal linings of the oral cavities in addition offer adorable route of administration for systematic drug delivery, improving drug therapeutic performance and often preferred by clinicians and patients. Liposomes are tiny spherical sacs of phospholipid molecules enclosing water droplets, formed (artificially) to carry drugs or other substances into the tissues by crossing and targeting to specific organelles. This work therefore focused on preparation of liposomes and liposomal buccal films (BFs) for potential buccal delivery of efavirenz, an ARVD model endowed with poor solubility and several side effects. The liposomes were prepared by thin film hydration method using crude soybean lecithin (CL) and cholesterol. Efavirenz loaded liposomes were evaluated for particle size, Zeta potential (ZP), morphology, encapsulation efficiency (EE%) and release kinetics studies. The physiochemical properties of the liposomes were also evaluated using Differential Scanning Calorimetry (DSC), X-ray diffraction (XRD), energy dispersity spectroscopy (EDS), and Fourier transform infrared (FTIR), while the formulation with the best encapsulation efficiency was used as the solvent medium for the buccal film formation. The buccal films were prepared using solvent casting method, where the liposomal suspension was used as the dispersing medium. The films were optimized for physical properties (thickness, weight variation and folding endurance) using digital Vernier calliper and digital weighing balance. The physiochemical properties of the selected BFs films made of Carbopol (CP) and its combination with Pluronic F127 (PF127) were further characterized using XRD, DSC, FTIR, Transmission Electron Microscopy (TEM), EDS and Scanning Electron Microscopy (SEM). The permeation study of the selected BFs was investigated using Franz diffusion cell. The BFs composed of CP alone or its combination with PF127 demonstrated much better bio-adhesive properties than the films made of other polymers (like Hydroxyl propyl methyl cellulose, HPMC) alone or in combination with PF127. The developed liposome formulation showed high encapsulation 98.8 ± 0.01 % in CL to cholesterol mass ratio of 1:1 and total lipid to drug mass ratio of 2:1. The average particle size 104.82 ± 2.29 nm and Zeta potential -50.33 ± 0.95 mV of these liposomes were found to be attractive for targeted delivery to the HIV infected cells. The CP based BFs (without and with PF127) exhibited good film thickness 0.88 ± 0.10 and 0.76 ± 0.14 mm, with weight uniformity 68.22 ± 1.04 and 86.28 ± 2. 16 mg, satisfactory flexibility values 258 and 321, and slightly acidic pH 6.43 ± 0.76 and 6.32 ± 0.01. The swelling percentage was found to be 50 % for CP film alone and 78 % for CP film with PF127. The cumulative amount of drug that permeated through the buccal epithelium over 24 hours was about 66 % from CP film alone and 75 % from CP film with PF127. Since no evidence of the liposomal encapsulation of EFV have been reported to our knowledge, we find the insights from the present study valuable as a set of preliminary data to encourage further investigations of the encapsulation and delivery of EFV like antiretrovirals for enhanced solubility, site targeting and prolonged release using crude soybean lecithin and mucoadhesive polymers, which holds some added economical values as naturally occurring lipid and polymeric mixtures as a promising delivery systems for buccal delivery of ARVDs.
Keywords: Liposomes; Highly active antiretroviral therapy; Antiretroviral agents; HIV infections -- Prevention